Original researchEvaluation of exercise capacity with cardiopulmonary exercise testing and BNP levels in adult patients with single or systemic right ventricles - Trojnarska, Olga; Gwizdała, Adrian; Katarzyński, Sławomir; Katarzyńska, Agnieszka; Oko-Sarnowska, Zofia; Bręborowicz, Piotr; Grajek, Stefan (Archives of Medical Science, 2010)
Introduction: The aim of the study was to evaluate exercise capacity using cardiopulmonary exercise test (CpET) and serum B-type natriuretic peptide (BNP) levels in patients with single or systemic right ventricles. Material and methods: The study group included 40 patients (16 males) – 17 with transposition of the great arteries after Senning operation, 13 with corrected transposition of the great arteries and 10 with single ventricle after Fontan operation, aged 19-55 years (mean 28.8 ±9.5 years). The control group included 22 healthy individuals (10 males) aged 23-49 years (mean 30.6 ±6.1 years). Results: The majority of patients reported good exercise tolerance – accordingly 27 were classified in NYHA class I (67.5%), 12 (30%) in class II, and only 1 (0.5%) in class III. Cardiopulmonary exercise test revealed significantly lower exercise capacity in study patients than in control subjects. In the study vs. control group VO2max was 21.7 ±5.9 vs. 34.2 ±7.4 ml/kg/min (p = 0.00001), maximum heart rate at peak exercise (HRmax) 152.5 ±32.3 vs. 187.2 ±15.6 bpm (p = 0.00001), VE/VCO2 slope 34.8 ±7.1 vs. 25.7 ±3.2 (p = 0.00001), forced vital capacity (FVC) 3.7 ±0.9l vs. 4.6 ±0.3 (p = 0.03), forced expiratory volume in 1 s (FEV1) 3.0 ±0.7 vs. 3.7 ±0.9l (p = 0.0002) respectively. Serum BNP concentrations were higher in study patients than in control subjects; 71.8 ±74.4 vs. 10.7 ±8.1 (pg/ml) respectively (p = 0.00001). No significant correlations between BNP levels and CpET parameters were found. Conclusions: Patients with a morphological right ventricle serving the systemic circulation and those with common ventricle physiology after Fontan operation show markedly reduced exercise capacity. They are also characterized by higher serum BNP concentrations, which do not however correlate with CpET parameters.